Report of the Indian Delegation on the Conference of Ministers of SAARC on Women and Family Health Kathmandu, Nepal 21st - 23rd November, 1993 - Planning Commission (Planning Commission, 1993)
The SAARC Ministerial Conference on Women and Family Health, held in Kathmandu in November 1993, convened representatives from all SAARC nations to address pressing issues related to women’s health, reproductive rights, and socio-economic empowerment. The conference highlighted critical challenges, including high maternal mortality, widespread anemia, early marriage, limited access to education, and persistent gender inequities across the region. Discussions emphasized the need for integrated approaches combining policy reforms, health service improvements, education initiatives, legal literacy programs, and poverty alleviation strategies. The Kathmandu Resolution, adopted at the conference, affirmed the commitment of member states to validate women’s rights, increase governmental support, and enhance international cooperation for resource mobilization. The document underscores that sustainable improvements in women’s health and family welfare require gender-sensitive governance, active participation of women in decision-making, and collaborative regional efforts, framing empowerment as central to socio-economic development in South Asia.
Department of Family Welfare Government of India
Department of Family Welfare Government of India
Keywords: SAARC; Women’s Health; Family Planning; Reproductive Health; Maternal Mortality; Gender Equality; Women Empowerment; Education; Legal Awareness; Nutrition; Policy Implementation; Kathmandu Resolution